Evaluation of Plasma Lipid Levels in Intrahepatic Cholestasis of Pregnancy - Şevki Çelen; Zahid Ağaoğlu; Merve Öztürk Ağaoğlu (Hitit Medical Journal, 2023)
Objective: To investigate the total cholesterol, triglyceride, LDL, VLDL, and HDL levels of pregnant women diagnosed with intrahepatic cholestasis of pregnancy and to examine the association with disease severity. Material and Method: A total of 80 pregnant women, 40 of whom were diagnosed with intrahepatic cholestasis of pregnancy, and 40 age-matched controls, were prospectively enrolled in this study. Lipid levels were compared among the case and controls, and their association with disease severity was analyzed. Birth weight, birth week, and neonatal outcomes were studied. Results: LDL and VLDL were significantly higher, and HDL levels were lower in the intrahepatic cholestasis of the pregnancy group than in the healthy pregnancies (p